(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify citizenship among university students, social responsibility, and the differences in citizenship among university students according to the gender variable (male-female), and the differences in social responsibility according to the gender variable (male-female), and to identify the correlation between citizenship and social responsibility The students of Al-Mustansiriya University.The sample consisted of (150) male and female students, which were chosen in a stratified random way from the students of the College of Education, Al-Mustansiriya University, in (9) departments. The number of males was (70) students and (80) females. The scale of (Al-Amer 2005) for citizenship was adopted, as it consisted of (40) items, and the scale of Al-Ezzi (2008) was adopted in relation to the social responsibility variable, which consisted of (42) items. The following results were reached:1- Citizenship among the current research sample